2019
DOI: 10.32722/epi.v16i2.2231
|View full text |Cite
|
Sign up to set email alerts
|

Persepsi Dosen Terhadap Penggunaan ICT Dalam Pembelajaran Bahasa Inggris

Abstract: __________________________________________________________________________ AbstrakStudi ini dilaksanakan untuk mengetahui bagaimana persepsi dosen terhadap penggunaan teknologi digital, yang biasa disebut information & communication technology (ICT), pada pembelajaran bahasa Inggris yang digunakan oleh dosen kepada mahasiswa. Metode penelitian yang digunakan adalah metode kualitatif dengan data kuantitatif. Dalam proses pengumpulan data, penulis menggunakan dua perangkat penelitian berupa kuesioner, dan wawanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
0
2
0
1
Order By: Relevance
“…One way is to introduce them to application sources that they can use as English learning media. With the development of the system embedded in a smartphone, now we can enjoy the many features and applications that can be downloaded on our smartphones (Ahmadi, 2018;Dewi et al, 2019). Thus, we can use the application to support learning, especially in learning English.…”
Section: Introductionmentioning
confidence: 99%
“…One way is to introduce them to application sources that they can use as English learning media. With the development of the system embedded in a smartphone, now we can enjoy the many features and applications that can be downloaded on our smartphones (Ahmadi, 2018;Dewi et al, 2019). Thus, we can use the application to support learning, especially in learning English.…”
Section: Introductionmentioning
confidence: 99%
“…Terdapat beberapa beberapa penelitian serupa mengenai persepsi penggunaan ICT dalam pembelajaran, diantaranya penelitian yang dilakukan oleh Salsabila, dkk yang melihat pandangan siswa terhadap penggunaan ICT berupa game edukasi (Salsabila et al, 2020), penelitian oleh Dewi, dkk yang melihat pandangan dosen dalam pembelajaran bahasa inggris (Dewi et al, 2019), serta penelitian oleh Parlindungan Perdede & Sunarto terkait pandangan guru dan siswa terhadap penggunaan TIK dalam pembelajaran (Parlindungan Pardede & Sunarto, 2020). Namun, dari penelitian diatas masih jarang penelitian yang berfokus pada pandangan mahasiswa matematika.…”
Section: Al-zubaidy 2019)unclassified
“…The use of ICT for passive voice learning has several considerations. Dewi et al, (2019) in her research discussed ICT for English language learning. The results showed that the lecturer argued that ICT was suitable for use in English language learning.…”
Section: Ictmentioning
confidence: 99%